POLA-POLA KOMUNIKASI DALAM INTERAKSI JUAL BELI DI PASAR LOAK “BLOK M” JEMBER - Siti Fatima; Andang Subaharianto; Edy Hariyadi (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2019)
This research observes the communication patterns in the buying and selling interactions that occur between buyers and sellers at the "Blok M" flea market in Jember. The object of research is focused on used book sellers, and used clothing sellers (babebo). The purpose of this study is to describe the communication patterns that are formed through the process of interaction and reveal the cultural themes contained in the buying and selling interaction activities between sellers and buyers in the Jember "Blok M" flea market. To achieve the research objectives ethnographic analysis of the James P. Spradley model is used which includes domain analysis, taxonomic analysis, compound analysis, and cultural themes. The results is in the buying and selling interactions in the Jember "Blok M" flea market, active sellers direct the interaction and passive buyers in responding to the point of the conversation. In buying and selling transactions with buyers, the services provided by used booksellers are very fast and the tempo of interaction used by sellers is very short. Perlokusi utterances made by used book sellers are done as an effort to establish good relations with buyers. If the relationship can be established more closely then the buyer will feel satisfied (satisfy) and will remain a customer. The cultural theme in the process of economic transactions between used book sellers and buyers is the establishment of socio-emotional ties in order to strengthen relations and mutual respect to help long-term economic cooperation.